Sudan : Final Review Under the 2002 Staff-Monitored Program and the 2003 Program; Sudan; Final Review Under the 2002 Staff-Monitored Program and the 2003 Program. (IMF Staff Country Reports; Country Report ;, 2003)
Executive Directors commended Sudan's efforts to bring economic policies back on track and welcomed the establishment of a mechanism to save oil export receipts arising from higher-than-programmed oil prices, but underscored the need to strengthen budget control and monitoring systems. The audit of the Sudan Petroleum Company (SPC) was completed, and netting operations by public enterprises and the private sector were abolished. The authorities' medium-term strategy aims at consolidating macroeconomic stability, sustaining economic growth, and reducing poverty.